Carbamazepine Induced Stevens-Johnson Syndrome That Developed into Toxic Epidermal Necrolysis: Review of the Literature - Yousef S. Abuzneid; Hussam I. A. Alzeerelhouseini; Duha Rabi; Ihab Hilail; Hatem Rjoob; Abdelrahman Rabee; Naser Amro; Qutaiba Qafisheh; Mohammad Kharraz (Case Reports in Dermatological Medicine)
Background. Stevens-Johnson syndrome and toxic epidermal necrolysis are both skin diseases believed to be following the pattern of a type IV hypersensitivity mechanism, which can be triggered by infectious agents or administration of a variety of drugs as part of the spectrum of severe cutaneous adverse reactions (SCARs). Fever and blisters, that peel forming painful raw areas, are early symptoms of this condition, and complications such as dehydration, sepsis, pneumonia, and multiple organ failure are typically seen during the course of the disease. Case Presentation. We present a case of a 23-year-old female patient referred to our hospital after taking carbamazepine and developing high-grade fever and ulcers that appeared initially in her mouth and face but then progressed despite treatment, extending all over her body and involving about 90% of her BSA. Conclusion. The use of IVIG and plasmapheresis was a good management for our case, helping in our patient’s well-being and recovery. Even if there is no stipulated guideline treatment for cases of SJS and TEN, we think that further investigations about IVIG and plasmapheresis should be investigated as a possible way to treat both conditions.